2022
DOI: 10.1177/10668969221113490
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Epstein-Barr Virus in Plasma Cell Neoplasms is Higher in HIV-Positive Individuals

Abstract: Aims. Epstein-Barr virus (EBV) is causally associated with many hematolymphoid malignancies. This laboratory-based study aimed to establish the prevalence of EBV in plasma cell neoplasms in a large South African cohort and to determine whether there is any correlation between EBV-positivity and human immunodeficiency virus (HIV) status in patients with plasma cell neoplasms, including plasma cell myeloma and plasmacytoma (solitary plasmacytoma of bone and extraosseous plasmacytoma). Methods. This single-instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…To date, little is known about the prevalence of EBV in PCNs in immunocompetent patients. Nael A et al reported that the EBV-positive rate of PCNs in immunocompetent patients was only 2.1% (3/141) in the United States, while Penzhorn IH et al reported that the EBV-positive rate of PCNs in immunocompetent patients was up to 16% (8/50) in South Africa 16,23 . In the present study, we retrospectively analyzed the EBV infection status in immunocompetent patients in south China.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…To date, little is known about the prevalence of EBV in PCNs in immunocompetent patients. Nael A et al reported that the EBV-positive rate of PCNs in immunocompetent patients was only 2.1% (3/141) in the United States, while Penzhorn IH et al reported that the EBV-positive rate of PCNs in immunocompetent patients was up to 16% (8/50) in South Africa 16,23 . In the present study, we retrospectively analyzed the EBV infection status in immunocompetent patients in south China.…”
Section: Discussionmentioning
confidence: 86%
“…Nael A et al reported that the EBV-positive rate of PCNs in immunocompetent patients was only 2.1% (3/141) in the United States, while Penzhorn IH et al reported that the EBV-positive rate of PCNs in immunocompetent patients was up to 16% (8/50) in South Africa. 16,23 In the present study, we retrospectively analyzed the EBV infection status in immunocompetent patients in south China. Our results revealed that the EBER-positive rate in PCNs in immunocompetent patients in south China was 12.3% (15/122), which seemed somewhat higher than that in west China (8.7%, 4/46; P = 0.349) and that in east China (6.9%, 4/58; P = 0.317), but the difference did not reach the statistical significance.…”
Section: Discussionmentioning
confidence: 99%